Perluasan Kewenangan Pengawasan Dewan Perwakilan Rakyat Republik Indonesia Berdasarkan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Hananto Widodo (Faculty of Law Hang Tuah University, 2020)
In general, there are at least 3 functions of the people's representative body. First, the function of legislation. Second, the supervisory function. Third, the budget function. This type of research used in this study is normative research. By using a statutory, conceptual and historical approach. The authority of the DPR's oversight before and after the amendment to the 1945 Constitution does not only lie in the regulation, where before the change is stipulated in the explanation and after the amendment to the 1945 Constitution is regulated in the Articles of the Constitution, but there is an expansion of the intended subject. In the 1945 Constitution prior to the amendment, the supervision of the House of Representatives was only addressed to the President whereas after the amendment to the 1945 Constitution the supervision of the House of Representatives was not only addressed to the President, but to all agencies or officials who carried out Government functions. The authority of the House of Representatives in conducting oversight becomes wider after the issuance of the Constitutional Court ruling No. 36 / PUU-XV / 2017, because independent state institutions, such as the Corruption Eradication Commission and the Election Commission can be subject to oversight by the House of Representatives.